The influences of volunteering and paid employment on older New Zealanders health related quality of life while testing for potential confounding variables - Shepherd, Gregory Stuart (Auckland University of Technology, 2010)
Utilizing the QHOQOL-BREF, which ascertains health related quality of life (HRQOL) across four domains, physical, psychology, social and environment, the effects of volunteering and paid employment on the HRQOL of older New Zealanders was assessed while testing four potential confounding variables, age, gender, income and extent of religious belief. About 65% of participants were involved in volunteer activity with about 13% involved in paid employment. Volunteer activity was associated with significantly enhanced HRQOL for three domains, physical, psychology and environment above and beyond the effects of potentially confounding variables. No significant HRQOL effects were revealed with respect to paid employment.